Application of the MIKE 21/3 coupled model to simulate the hydrodynamic regime in the Tra Khuc River Estuary, Quang Ngai Province - Dao, Dinh Cham; Kirill, Ganzey; Dao, Thi Thao; Dang, Thi Hong Nhung; Hoang, Thai Binh (Vietnam Journal of Marine Science and Technology, 2025)
This study applies the MIKE 21/3 Couple model to simulate the hydrodynamic regime of the Tra Khuc River estuary. The model was calibrated and validated using observed water level and wave data from the study area, with evaluation metrics indicating good performance. Simulations were carried out for two monsoon scenarios (Southwest and Northeast). The results show that during the Southwest monsoon, the current mainly flows along the shoreline from south to north, with an average velocity of about 0.05–0.15 m/s; average wave height in offshore areas is greater than 0.8m, while in the estuary it ranges from 0.2 to 0.4 m. During the Northeast monsoon, both current velocities and wave heights are higher compared to the Southwest monsoon. The average current velocity is 0.05–0.25 m/s, flowing from north to south, and offshore wave heights range from 3.6 to 4.0 m, with some areas exceeding 4.0 m. The findings provide an essential scientific basis for sediment transport assessment and for developing coastal management and planning strategies in Quang Ngai Province.